The role of international livestock research in addressing human needs and the environment - Li Pun, H.H.; Maass, Brigitte L. (1999)
The demand for livestock products is growing fast in developing countries due to population growth, urbanization, and rising incomes. For example from 1990 to the year 2010, demands for meat and milk in developing countries were estimated to grow by 66 percent and 223 percent, respectively. In most developing countries, however, livestock also fulfil a role as source of traction, fertilizer, savings, and social prestige. Particularly in developing countries many environmental concerns relate to animal production. Therefore, major challenges and opportunities lie in developing sustainable production systems through holistic and multidisciplinary research and implementing them in partnerships with national and international organizations, given the complexity of the matter.